64.1k views
0 votes
Given g(x) = -2x^2 + x + 6 determine: [g(x+h) - g(x)] / h

Given g(x) = -2x^2 + x + 6 determine: [g(x+h) - g(x)] / h-example-1
User Albuvee
by
5.8k points

1 Answer

5 votes

Task: determine [g(x+h) - g(x)] / h

1. Starting with g(x) = -2x^2 + x + 6, determine g(x+h):

g(x+h) = -2(x+h)^2 + (x+h) + 6 = -2(x^2 + 2xh + h^2) + x + h + 6

=

2. Subtract g(x) from g(x+h):

g(x+h) - g(x) = -2x^2 - 4xh -2 h^2 + x + h + 6

- (2x^2 + x + 6 )

--------------------------------------------------------

= - 4xh - 2h^2 + h

3. Divide this result by h:

g(x+h) - g(x)

------------------ = -4x - 2h + 1 (answer)

h


Note: Soon you will begin taking the limit (as h approaches 0) of such results. Here that result would be -4x - 2(0) + 1 = -4x + 1. This algebraic quantity is the "derivative" of the given function g(x) = -2x^2 + x + 6.

User Sascha Gottfried
by
5.9k points